Complexity of the prey spectrum of Agaronia propatula (Caenogastropoda: Olividae), a dominant predator in sandy beach ecosystems of Pacific Central America - Robinson, Nathan J.; Peters, Winfried S. (PeerJ, 2018)
Olivid gastropods of the genus Agaronia are dominant predators within invertebrate communities on sandy beaches throughout Pacific Central America. At Playa Grande, on the Pacific Coast of Costa Rica, we observed 327 natural predation events by Agaronia propatula. For each predation event, we documented prey taxa and body size of both predator and prey. The relationship between predator and prey size differed for each of the four main prey taxa: bivalves, crustaceans, heterospecific gastropods, and conspecific gastropods (representing cannibalism). For bivalve prey, there was increased variance in prey size with increasing predator size. Crustaceans were likely subdued only if injured or otherwise incapacitated. Heterospecific gastropods (mostly Olivella semistriata) constituted half of all prey items, but were only captured by small and intermediately sized A. propatula. Large O. semistriata appeared capable of avoiding predation by A. propatula. Cannibalism was more prevalent among large A. propatula than previously estimated. Our findings suggested ontogenetic niche shifts in A. propatula and a significant role of cannibalism in its population dynamics. Also indicated were size-dependent defensive behavior in some prey taxa and a dynamic, fine-scale zonation of the beach. The unexpected complexity of the trophic relations of A. propatula was only revealed though analysis of individual predation events. This highlights the need for detailed investigations into the trophic ecology of marine invertebrates to understand the factors driving ecosystem structuring in sandy beaches.
Keywords: Agaronia; Ontogenetic niche shift; Trophic network; Predator–prey interaction; Sandy beach; Olividae; Cannibalism; Tropical Eastern Pacific